CONCERNS OF ACCOUNTING TEACHERS IN IMPLEMENTING GHANA'S 2007 EDUCATION REFORM: REVISITED - Dr. Joseph Tufuor Kwarteng (Informascope, 2016)
The purpose of the study was to find out whether time improved the concerns of accounting teachers in the implementation of the senior high school accounting curriculum since the works of Ankomah and Author (2010a) and Author (2009) some 6 years ago. It was a replication of these two studies which drew from the recommendations made by the authors to follow up on their earlier studies. The study drew 159 senior high school accounting teachers from 3 of the 10 administrative regions in Ghana. The 159 participating accounting teachers were surveyed with the Stages of Concern Questionnaire (SoCQ). Only practicing senior high school accounting teachers were recruited to respond to the SoCQ. The study found that the senior high school accounting teachers were mainly non-users of the accounting curriculum. They had both the primary and secondary concerns at the awareness and informational stages respectively. For that matter, they were not very much involved in the delivery of the curriculum.